Expression of the Cavin Family in Childhood Leukemia and Its Implications in Subtype Diagnosis and Prognosis Evaluation - Yang, Jing; Huang, Junbin; Wang, Huabin; Liu, Yong; Tang, Yanlai; Lin, Chao; Zhou, Qin; Chen, Chun (Frontiers in Pediatrics, 2022)
Background: Caveolae are plasma membrane subdomains of many mammalian cells that play critical roles in cellular processes, including endocytosis, signal transduction and tumorigenesis. Cavin proteins are essential for caveola formation, structure and function and are reported to be involved in various human diseases, but little is known about their expression and prognostic value in leukemia. Methods: We performed a detailed analysis of Cavin family mRNA expression levels in different cancer tissues versus normal tissues via the ONCOMINE, Gene Expression Profiling Interactive Analysis (GEPIA) and Cancer Cell Line Encyclopedia (CCLE) databases. Then, we used RT-qPCR and Western blotting to validate Cavin1-4 expression in 10 fresh leukemia samples. Moreover, we estimated their prognostic value in leukemia with the R programming language and GEPIA database. Results: Cavin expression is decreased in most human cancers, especially leukemia. Cavin2 is often overexpressed in myeloid leukemia but downregulated in lymphoblastic leukemia, and Cavin4 has the opposite pattern. Interestingly, Cavin1 and Cavin3 are not correlated with survival, but low Cavin4 expression is associated with poorer overall survival (OS), while low Cavin2 expression is associated with a significantly better leukemia prognosis. Previous studies have shown that high Cavin2 expression facilitates caveolin-1 recruitment and colocalization and that caveolin-1 is positively correlated with multidrug resistance-1 (MDR-1) gene expression in relapsed leukemia. The coordinated overexpression of Cavin2 and caveolin-1 leads to compartmentation into caveolae, which prevents epidermal growth factor receptor (EGFR) degradation and simultaneously enables intracellular EGFR kinase-linked signaling. Conclusion: The Cavin family showed significant expression differences between cancer and normal tissues, especially in human leukemia. High Cavin2 and low Cavin4 levels predict poor survival and could be promising subtype diagnosis and prognosis biomarkers for leukemia.